Cross-sectional associations of neighborhood third places with social health among community-dwelling older adults. (August 2020) - Lane, Anna P.; Hou, Yuting; Hooi Wong, Chek; Yuen, Belinda
Abstract: Social health is a key aspect of active ageing. The objectives of this study are to investigate whether and what type of neighborhood third places are associated with positive social health among community dwelling older adults, and explore whether the associations vary by gender. Neighborhood third places are those spaces that have a social function and are located within a neighborhood, but outside the home (first place) and work (second place). Cross-sectional data were from 981 adults aged 55 years and older who responded to a survey conducted in 2018 in three Singapore neighborhoods. The neighborhoods were selected because they have a high percentage of older residents, different housing typologies, and heterogeneity of built environment qualities. Social health was measured using the six-item Lubben Social Network Scale. Attributes of participants' physical environment included residential density, pedestrian-friendly street design, access to public transport, and were objectively assessed using geographic information systems data. Covariates included age, sex, ethnic group, highest educational qualification, marital status, number of people living in dwelling, years living at current address, dwelling unit type, and number of diagnosed medical conditions and IADLs. Regression analysis was performed using Stata version 15 and indicated that female respondents who live in closer proximity to a wet market were more likely to have higher levels of social health independently of individual demographic and physical health characteristics, physical environment qualities, and other destination types. In a time of heightened concern about social isolation and loneliness among older age groups, this study contributes evidence that older people, particularly females, who live in closer proximity to a wet market self-reported better social health. Wet markets are spaces where people can mingle while purchasing or bargaining for fresh produce and household necessities. The mechanisms via which neighborhood third places may contribute to social health requires examination. Highlights: Places located within neighborhoods and outside of the home have a social function. Which third places are connected with better social health of older adults is unknown. Older women, but not men, living closer to a wet market reported better social health. Provides novel insights on third places and older people's social health in Singapore. Emphasizes importance of collaboration between public health and urban planning.